pengembangan kreativitas sisw sd melalui seni tari: Mengembangkan Kreativitas siswa SD melalui tari pendidikan - Putri, Siti Putri Fitriah (Jurnal Pendidikan Sendratasik, 2025)
This research stems from the issue in several elementary schools that have not yet provided space for students to express and develop their creativity, particularly in dance education. Dance learning activities are often conducted separately and are not integrated with other forms of art, even though one of the main goals of basic education is to foster students' creativity. Creativity is defined as the ability to generate new, imaginative, and useful ideas. To address this challenge, the study proposes an educational dance approach based on free expression in learning activities. This approach encourages students to express themselves freely without fear of making mistakes, resulting in original and natural expressions. The aim of this study is to explore how the implementation of a free-expression approach in dance education can foster the growth of students' creativity. The research uses a descriptive qualitative method. The results show that this approach can develop students’ creativity through several aspects: 1) the creative potential of elementary students before the implementation of dance learning, 2) the planning of materials, indicators, objectives, and learning steps, 3) the implementation of the learning process using a free-expression approach to enhance creativity, and 4) the evaluation conducted during the learning process.